2022
DOI: 10.1111/hsc.13848
|View full text |Cite
|
Sign up to set email alerts
|

'No Matter How Harsh, We Are Alive': Coping Strategies of Rural–Urban Migrant Homeless Older People in Ethiopia

Abstract: The prevalence of homelessness among older adults in Ethiopia is growing. While prior studies examined the push factors and challenges of homeless elders, little is known about how older people cope with homelessness in a context of limited ageing services. This study explored the coping strategies of homeless older people in Kobo Town, Ethiopia. Purposive sampling was used to identify 10 homeless older people and four key informants. Thematic analysis was used to analyse the data collected through in‐depth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Instead, over time they are steadily losing their stature as valuable members of Ethiopian society. When younger family members migrate from rural areas or take over older adults’ assets, older adults are left to fend for themselves ( Gebeyaw et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, over time they are steadily losing their stature as valuable members of Ethiopian society. When younger family members migrate from rural areas or take over older adults’ assets, older adults are left to fend for themselves ( Gebeyaw et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increases in the cost of living (currently at 39%) have pushed many to leave their rural homesteads looking for ways to fulfill their basic needs, either through work, begging, or other alternatives. The same is true for older adults who were previously able to get their basic needs met within their extended families in their original birthplace ( Gebeyaw et al, 2022 ). Older adults are the primary victims of the increased cost of living as they are left aside by younger relatives who increasingly migrate from rural areas to towns in search of better income ( Tegegne & Penker, 2016 ).…”
Section: Challenges Of the Growing Older Population In Ethiopiamentioning
confidence: 91%
See 1 more Smart Citation
“…Interestingly, though most other studies emphasize how the lack of emotional security and helplessness associated with homelessness results in challenges building goals or considering future prospects (e.g., Williams & Stickley, 2011;Goodman et al, 1991;Bentley, 1994), one other study on happiness and future expectations of homeless people in Nicaragua had similar findings to this study in that participants had positive future expectations in spite of seeing the current situation as negative or challenging (Vasquez & Berrios, 2022). This aligns with a growing body of research that considers the intersections of hope and homelessness, varying from thematic analysis of individual perceptions to more practical coping strategies and resilience (Duncan et al, 2022;Durbin et al, 2019;Gebeyaw et al, 2022). This study distinguishes 125 itself from these works by considering protective factors identified by participants themselves and the ways in which these intersect to create dynamic experiences of agency in lived experiences.…”
Section: Discussionmentioning
confidence: 82%